The Influence of Safety Leadership Through Safety Behaviour on Work Accident in Can Department of PT. XYZ - Faradico, Ariesto Christopher; Sary, Fetty Poerwita (PT FORMOSA CENDEKIA GLOBAL, 2024)
PT. XYZ has a worrying rate of work accidents in the canning department. This is not in accordance with the company's target of